Indicadores de projeto para edifícios em alvenaria estrutural - Freire, Ailton Soares (Universidade Federal de São Carlos, 2007)
This work deals on the identification and quantification of pointers of project of buildings in structural masonry. Several projects of different types are analyzed from which each material is quantified relative to the characteristics of each construction. Project pointers were then assessed. The calculated pointers can propitiate the identification of factors of the construction and criteria of project that contribute for the rise or the reduction in the consumption of materials. The pointers can represent important tool for the designer engineer, as they can serve as reference values for gauging projects in development. Additionally, the consumption pointers also are important for the planning and budget of new enterprises. It is believed that several aspects of this research had been very few referenced before, such as the case of consume rate of steel and concrete in transition structures, the consume of different block types in relation to the floor area, the average floor load, the steel rate in structural masonry, among others
Keywords: Edificações; Alvenaria estrutural; Análise de projetos; Gestão de projetos; Indicadores; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL